Cancer Control Related to Stimulation of Immunity by Low-Dose Radiation - Shu-Zheng Liu (SAGE Publishing, 2007)
Previous studies showed that low dose radiation (LDR) could stimulate the immune system in both animal and human populations. This paper reviews the present status of relevant research as support to the use of LDR in clinical practice for cancer prevention and treatment. It has been demonstrated that radiation-induced changes in immune activity follows an inverse J-shaped curve, i.e., low dose stimulation and high dose suppression. The stimulation of immunity by LDR concerns most anticancer parameters, including antibody formation, natural killer activity, secretion of interferon and other cytokines as well as other cellular changes. Animal studies have revealed that LDR retards tumor growth, decreases cancer metastasis, and inhibits carcinogenesis induced by high dose radiation. These effects of LDR on cancer control were found to be related to its stimulation on immunity. The experimental data may well explain the efficacy of the clinical trial of LDR in the treatment of cancer.